Diketopiperazines and arylethylamides produced by Schizophyllum commune, an endophytic fungus in Alchornea glandulosa - Biasetto, Carolina Rabal [UNESP]; Somensi, Andressa [UNESP]; Figueiro, Fernanda Sales; De Moraes, Luiz Alberto Beraldo; Silva, Geraldo Humberto; Marx Young, Maria Claudia; Da Silva Bolzani, Vanderlan [UNESP]; Araújo, Angela Regina [UNESP] (Ecletica Quimica, 2019)
Chemical investigation of the crude PDB extract obtained from the endophytic fungus Schizophyllum commune afforded the pure substances, cyclo(L-Pro-L-Val) (1), uracil (2), cyclo(Pro-Tyr) (3), p-hydroxybenzoic acid (4) and a mixture of Rel.cyclo(Pro-Phe) (5) and Rel.cyclo(Pro-Ile) (6). When cultured in corn, the extract of this fungus yielded N-(2-phenylethyl) acetamide (7) and N-(4hydroxyphenylethyl) acetamide (8). The structures of all compounds were determined based on the analyses of their MS, 1D and 2D-NMR spectroscopic data. Analysis of the crude extracts obtained from small-scale cultures (in PBD, YM, Nutrient, Czapek, Malt Extract, Corn and Rice) and a large-scale culture (in PDB) by mass spectrometry showed the presence of diketopiperazines 1, 3, 5 and 6. The crude extracts showed promising antioxidant, antifungal and acetylcholinesterase (AChE) inhibitory activities. The metabolites 7 and 8 showed antifungal and AChE inhibitory activities in vitro. This is the first report of the identification and isolation of diketopiperazines, arylethylamides, p-hydroxybenzoic acid in endophytic fungus of the Schizophyllum genus.
Keywords: Alchornea glandulosa; Arylethylamides; Diketopiperazines; Endophytic fungi; Schizophyllum commune